Reduced cell surface levels of GPI‐linked markers in a new case with PIGG loss of function. Issue 10 (12th June 2017) - Zhao, Jin James; Halvardson, Jonatan; Knaus, Alexej; Georgii‐Hemming, Patrik; Baeck, Peter; Krawitz, Peter M.; Thuresson, Ann‐Charlotte; Feuk, Lars
Abstract : Glycosylphosphatidylinositol (GPI) is a glycolipid that anchors proteins to the cell surface. Pathogenic variation in genes involved in GPI synthesis is associated with intellectual disability syndromes caused by GPI deficiency. Our results show that nonsense variation in the PIGG gene is associated with intellectual disability, but that expression of GPI‐anchored proteins (GPI‐AP) in patients differs between cell types, with reduced expression in patient fibroblasts, but not in patient granulocytes. Abstract: Glycosylphosphatidylinositol (GPI) is a glycolipid that tethers more than 150 different proteins to the cell surface. Aberrations in biosynthesis of GPI anchors cause congenital disorders of glycosylation with clinical features including intellectual disability (ID), seizures, and facial dysmorphism. Here, we present two siblings with ID, cerebellar hypoplasia, cerebellar ataxia, early‐onset seizures, and minor facial dysmorphology. Using exome sequencing, we identified a homozygous nonsense variant (NM_001127178.1:c.1640G>A, p.Trp547*) in the gene Phosphatidylinositol Glycan Anchor Biosynthesis, Class G ( PIGG ) in both the patients. Variants in several other GPI anchor synthesis genes lead to a reduced expression of GPI‐anchored proteins (GPI‐APs) that can be measured by flow cytometry. No significant differences in GPI‐APs could be detected in patient granulocytes, consistent with recent findings. However, fibroblasts showed a reduced global level of GPI anchors and of specific GPI‐linked markers. These findings suggest that fibroblasts might be more sensitive to pathogenic variants in GPI synthesis pathway and are well suited to screen for GPI‐anchor deficiencies. Based on genetic and functional evidence, we confirm that pathogenic variants in PIGG cause an ID syndrome, and we find that loss of function of PIGG is associated with GPI deficiency.